Molecular Profiling of Lipase-Producing Bacillus spp. from Basrah Extreme Soils - Waad Blaasm Abd Alsada; Ismaal jmia Abas (Universitas Muhammadiyah Sidoarjo, 2026)
General Background: Lipases are hydrolytic enzymes with broad industrial applications due to their catalytic versatility and environmental relevance. Specific Background: Oil-contaminated and extreme environments represent promising reservoirs for robust lipase-producing bacteria. Knowledge Gap: Limited molecular characterization has been conducted on indigenous lipolytic Bacillus species from extreme sites in Basrah Governorate. Aim: This study aimed to isolate, screen, and molecularly identify lipase-producing Bacillus spp. from oil-affected soils and related environments. Results: Ten samples were collected, and five high-performing isolates were confirmed through Spirit Blue Agar and Rhodamine B assays. Optimal lipase production occurred at 37°C, pH 7, after 48 hours using olive oil as substrate. 16S rRNA sequencing identified the isolates as Bacillus velezensis, Bacillus subtilis, Bacillus tequilensis, Bacillus licheniformis, and Bacillus cereus, with sequence similarities ranging from 98.88% to 99.82%. Novelty: This study provides molecular evidence of diverse indigenous lipolytic Bacillus strains from Basrah’s extreme habitats. Implications: The findings support their prospective application in biofuel production, wastewater treatment, and industrial biocatalysis.Highlights: Dual-media screening strengthened qualitative detection of lipase activity. Molecular identification confirmed five high-similarity Bacillus strains. Extreme Basrah soils serve as reservoirs of industrially relevant lipolytic bacteria. Keywords: Lipase-Producing Bacteria, Bacillus Spp., 16S rRNA Sequencing, Oil-Contaminated Soil, Industrial Biotechnology